Perbandingan Pendapat Mazhab Syafi’i Dengan Madzhab Maliki Dalam Praktik Ibadah Masyarakat Muslim Di Indonesia - Syaifudin Ahyar muhamad; Tahiyatul Firda; Nasrul Hidayanto; Anita Safitri; Siyono (Yayasan Nanggroe Aceh Mulia, 2026)
Indonesia, as the country with the largest Muslim population in the world, possesses a dynamic and diverse religious tradition. Historically, the Shāfiʿī school of law has been the dominant reference for Muslim religious practices in Indonesia through the role of Shāfiʿī scholars and Islamic educational institutions such as pesantren. However, the development of information technology and globalization has expanded access to cross-madhhab literature, including the Mālikī school, which offers more contextual legal approaches in certain aspects of worship. This condition has led to variations in religious practices and, at the same time, potential confusion among Muslim communities. This study aims to analyze the historical background and methodological characteristics of the Shāfiʿī and Mālikī schools of law and to compare their similarities and differences in worship practices relevant to contemporary Indonesian Muslims. This research employs a library research method with a qualitative descriptive-analytical approach. Data were collected from primary sources in the form of classical fiqh texts of both schools and secondary sources such as books and scholarly articles. Data analysis was conducted through data selection, presentation, and conclusion drawing, supported by source triangulation to ensure validity. The findings indicate that differences in worship practices between the Shāfiʿī and Mālikī schools stem primarily from variations in their uṣūl al-fiqh methodologies, particularly in the use of textual evidence, the practice of the people of Madinah, and considerations of public interest (maṣlaḥah). These differences are not contradictory but reflect the richness and flexibility of Islamic jurisprudence. This study underscores the importance of comparative fiqh literacy in fostering religious moderation and mutual respect within Indonesia’s plural Muslim society.